2019
DOI: 10.1103/physrevd.100.054037
|View full text |Cite
|
Sign up to set email alerts
|

Novel scheme for parametrizing the chemical freeze-out surface in heavy ion collision experiments

Abstract: We introduce a new prescription for obtaining the chemical freeze-out parameters in the heavyion collision experiments using the Hadron Resonance Gas model. The scheme is found to reliably estimate the freeze-out parameters and predict the hadron yield ratios, which themselves were never used in the parametrization procedure.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 102 publications
1
10
0
Order By: Relevance
“…It is very important to study the behavior of and due to their relation to map the phase diagram of Quantum Chromodynamics (QCD), though is usually used [ 11 , 12 , 13 , 14 , 15 , 16 ] in the phase diagram. In order to extract and , and study their dependence on energy, we can analyze the ( ) spectra of particles using different models.…”
Section: Introductionmentioning
confidence: 99%
“…It is very important to study the behavior of and due to their relation to map the phase diagram of Quantum Chromodynamics (QCD), though is usually used [ 11 , 12 , 13 , 14 , 15 , 16 ] in the phase diagram. In order to extract and , and study their dependence on energy, we can analyze the ( ) spectra of particles using different models.…”
Section: Introductionmentioning
confidence: 99%
“…Following the complication regarding the chosen set of ratios, we have introduced an alternative method in Ref. [29]. The individual hadrons are not a conserved quantity in the strong interaction.…”
Section: Advances In High Energy Physicsmentioning
confidence: 99%
“…In a recent work [28], we have shown that in χ 2 analysis, a larger systematic variation can arise depending on the chosen set of ratios. A conserved-charge-dependent extraction of thermal parameters has been proposed [29], which seems to suitably estimate thermal parameters and predict equilibration in the most central collision. It will be interesting to check the centrality variation of thermal parameters and the equilibration of strange particles in this framework.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent work [109], we proposed an alternate scheme to the χ 2 analysis for studying the freeze-out characteristics. The basis of that work was to argue that one should use the quantities associated with various conserved charges of strong interactions to obtain the freezeout parameters.…”
Section: B Hadron Yield Ratiosmentioning
confidence: 99%